CONCRETE CREEP THEORY MODELS AND THEIR FINITE-ELEMENT IMPLEMENTATION - Petr Pavlovich Gaydzhurov; Elvira Rashidovna Iskhakova (Advanced Engineering Research, 2012)
The finite-element method for the plane problem solution of the concrete creep theory with regard to aging is developed. The expressions based on the formulas for creep values proposed by N. K. Arutyunyan and S. V. Alexandrovsky are used as the hereditary functions of the second kind. The friendly programming expressions for the concrete relaxation kernels are obtained by the symbolic processor. The durable step-by-step algorithm and the appropriate software for performing accounting under the variable loading with regard to the fast incident creep at the initial load and partial reversibility of the creep flow under deloading are developed. The verification of the developed software is carried out on the base of the available experimental data on the creep of the directly compressive prismatic concrete rods and bending concrete beams.